Engagement within E-learning - An evaluation of an online course for professionals from an engagement perspective - Emanuelsson, Karl; Gustafsson, Elvira (My University, 2021)
The world is rapidly transforming into an increasingly digital society which has a great influence on people’s everyday lives. The digital transformation is also affecting the education system, where complete courses or even full education programs are conducted in an online environment. Engagement is generally seen as an important factor for successful learning, and some research claim engagement as even more fundamental within E-learning. Therefore, the purpose of this study was: (1) to measure the level of engagement of the participants in the teacher free E-learning course Agenda 2030-linsen, provided by Miljöbron, from a multidimensional construct with the three dimensions behavioural, affective and cognitive engagement; and (2) to provide design recommendations for Miljöbron on adaptations for increasing the engagement. In order to answer the stated purpose, an instrument was developed, consisting of five questionnaires where each was representing the learning activities Text, Film, Self-reflection, Quiz and Pairing, and Workshop, that were identified via a course review. Each questionnaire was implemented in Agenda 2030-linsen and based on the amount of collected data, analyses were executed on all except Workshop. The results revealed that the course generates a relatively high engagement throughout all dimensions of engagement and learning activities, though the behavioural was significantly lower than both the affective and cognitive, in total. Thus, it is concluded that no major adaptations are needed to be done, but the recommendations provided regard measures that sought to increase the behavioural engagement.
Keywords: behavioural engagement; affective engagement; cognitive engagement; multidimensional construct; measuring engagement; E-learning